Batman & Robin cuirs no cinema brasileiro : o camp, o artifício e a afetação em “Batguano” (2014) - Nobre, Lusergio Matos (2023)
The feature film from Paraíba “Batguano” (2014), by Tavinho Teixeira, presents for the first time in a filmic work, the queer version of the duo Batman and Robin, comic book superheroes who became popular in the 20th century and who, now, they form a couple and, aged and decadent, face a deadly epidemic. It is intended to investigate, in an interdisciplinary way, the filmic representation of these superheroes, as subjects queers from the use of the category camp and its evident marks of artifice and exaggeration and from post-structuralist sex-gender studies. In this way, the objective is to analyze aesthetic and narrative elements that point to: (i) the use of camp sensibility in art direction and in the mise-en-scène, (ii) the devices, (iii) the metalinguistic resources and the (iv) performative theatricality, categories that reinforce the classification of the film as a queer cinema”, as well as reflect on the aging of superheroes as a dystopian place, from the intersection of age with the categories of gender and sexuality. Finally, we point out that Tavinho's film is a queer work, due to its unique aesthetic sensitivity, a cinematography that subverts expectations, represents diversity and deconstructs stereotypes linked to aging gay men.